Migrants and religion paths, issues, and lenses : a multidisciplinary and multi-sited study on the role of religious belongings in migratory and integration processes - Zanfrini, Laura (Leiden Boston Brill, 2020)
Introduction. General description of the study, key issues, and provisional conclusions / Laura Zanfrini -- The uncanny "religious" refugee : a post-secular perspective on ethics of hospitality / Paolo Gomarasca -- Religion in secularized and post-secularized Europe / Monica Martinelli -- Migration and religious freedom : the legislative and judicial framework at international and European level / Andrea Santini and Monica Spatti -- No size fits all : diversity, state and politics in the contemporary Middle East / Paolo Maggiolini, Andrea Plebani and Riccardo Redaelli -- Christians navigating through middle east turbulences : the case of the Copts in Egypt / Alessia Melcangi and Paolo Maggiolini -- Religious affiliations and social coexistence in the Islamic Middle East countries / Giancarlo Rovati -- Women's rights and Shari'a Law in the MENA region / Vera Lomazzi -- The "place" of religion in the Italian asylum seekers' reception system : constitutional, legislative and procedural framework / Paolo Bonetti -- On the role of religion in the decision to migrate / Laura Zanfrini -- The "space" of religion in the assessment of asylum applications / Laura Zanfrini -- On the role of religion in the process of adaptation of (forced) migrants / Laura Zanfrini and Mario Antonelli -- Religion and integration : issues from international literature / Annavittoria Sarli and Giulia Mezzetti -- Religious persecution, migrations and practices in faith-based organizations : some recommendations from a qualitative study / Lucia Boccacin and Linda Lombi -- Interreligious dialogue in the governance of migration and inter-ethnic cohabitation / Fabio Baggio -- The multi-ethnic and multi-religious transformation of the largest diocese in the world : the Church of Milan and the "Synod from the Peoples" / Laura Zanfrini and Luca Bressan -- Migrations and intergenerational religious transmission : issues from international literature / Donatella Bramanti, Stefania Meda and Giovanna Rossi -- The Copts in Italy : migration and generosity / Beatrice Nicolini -- Religious belonging and (forced) migration : a study on migrant Coptic families in Italy / Cristina Giuliani and Camillo Regalia -- Religious belonging and (forced) migration : a study on migrant Coptic minors in Italy / Giovanni Giulio Valtolina and Paola Barachetti -- The religious dimension in plural schools : institutional, relational and strategic issues / Maddalena Colombo -- Religious belonging in multicultural schools : freedom of expression and citizenship values / Rosangela Lodigiani -- Religious conflicts in multicultural schools : a generational divide between students and adults / Mariagrazia Santagati -- Religions and Laïcité in the French republican school / Alessandro Bergamaschi and Catherine Blaya -- Religious education in schools as a necessity in a secular state : the perspective in Catalonia / Núria Llevot-Calvet, Olga Bernad-Cavero and Jordi Garreta-Bochaca.
"Despite the worldwide dramatic spread of religious-based discriminations, persecutions, and conflicts, both official data and academic literature have underestimated their role as a root cause of contemporary migrations. This multidisciplinary study aims to overcome this gap. Through an unprecedented collection of theoretical analysis and original empirical evidence, the book provides unique data and insights on the role of religion in the trajectories of asylum seekers and migrants - from the analysis of the religious geography of sending countries to the role of spirituality as a factor of resilience and adaptation. By enhancing both academic and political debate on these issues, the book offers the possibility of regaining awareness of the close link between religious freedom and the quality of democracy"--
Includes bibliographical references and index
Keywords: Emigration and immigration -- Religious aspects -- Case studies; Religious refugees -- Social conditions -- Case studies; Immigrants -- Religious life -- Case studies; Freedom Of Religion; Belonging (Social psychology)